2019
DOI: 10.3390/molecules24010144
|View full text |Cite
|
Sign up to set email alerts
|

Structure Identification of ViceninII Extracted from Dendrobium officinale and the Reversal of TGF-β1-Induced Epithelial–Mesenchymal Transition in Lung Adenocarcinoma Cells through TGF-β/Smad and PI3K/Akt/mTOR Signaling Pathways

Abstract: ViceninII is a naturally flavonoid glycoside extracted from Dendrobium officinale, a precious Chinese traditional herb, has been proven to be valuable for cancer treatment. Transforming growth factor-β1 (TGF-β1), promotes the induction of epithelial–mesenchymal transition (EMT), a process involved in the metastasis of cells that leads to enhanced migration and invasion. However, there is no previously evidence that ViceninII has an inhibitory effect on cancer metastasis, specifically on the TGF-β1-induced EMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 63 publications
(78 reference statements)
1
36
0
Order By: Relevance
“…Through targeting the PI3K/Akt pathway, CNTN-1 boosted chemoresistance in LUAD via abduction of EMT [21]. Studies have indicated that the expression levels of some vital factors (such as E-cadherin, Ncadherin, Vimentin and MMP-9) have been detected during the process of EMT [22,23]. As reported, Ecadherin is a suppressor, whereas N-cadherin, Vimentin and MMP-9 are promoters [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…Through targeting the PI3K/Akt pathway, CNTN-1 boosted chemoresistance in LUAD via abduction of EMT [21]. Studies have indicated that the expression levels of some vital factors (such as E-cadherin, Ncadherin, Vimentin and MMP-9) have been detected during the process of EMT [22,23]. As reported, Ecadherin is a suppressor, whereas N-cadherin, Vimentin and MMP-9 are promoters [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, the TGF-β/Smad pathway also has a negative feedback mechanism mediated through Smad7 competitive binding to TGFBR1 and blocking the TGF-β/Smad pathway signalling [ 10 ]. For the non-canonical TGF-β pathway, the activated TGF-β crosstalks with other signalling pathways, such as Rho, phosphoinositide 3-kinase (PI3K), and mitogen-activated protein kinase (MAPK) signalling cascades, to promote EMT [ 11 ], cancer invasion [ 12 ], and angiogenesis [ 13 ]. In consequence, both the canonical and non-canonical TGF-β pathways play an important role in cancer progression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…C-glycosylflavones are critical in plant physiology and are beneficial for human health. For example, vicenin-2 is an effective flavone that shows anti-inflammatory 6 , antiglycating 7 , antispasmodic 8 , antiseptic 9 , antiplatelet, antithrombotic 10 , and anticancer 11,12 activity. Because flavonoids show such high biological activity, determining the pathways involved in the biosynthesis of flavonoid glycosides is important.…”
Section: Introductionmentioning
confidence: 99%